Erratum and Addendum: “A Standalone PV System with a Hybrid P&O MPPT Optimization Technique” - Hota, S.; Sahu, M. K.; Malla, J. M. R. (Engineering, Technology & Applied Science Research, 2020)
Since the publication of our original paper in vol. 7, no. 6 of this journal [1], we have detected several misprints and errors that are corrected here, in the order in which they appear in the original paper.